Resistance of Argopecten purpuratus scallop larvae to vibriosis is associated with the front-loading of immune genes and enhanced antimicrobial response - Jeria, Eduardo; Oyanedel, Daniel; Rojas, Rodrigo; Farlora, Rodolfo; Lira, German; Mercado, Ana; Muñoz, Katherine; Destoumieux-Garzón, Delphine; Brokordt, Katherina; Schmitt, Paulina (Frontiers in Immunology, 2023)
Mass mortality events caused by vibriosis have emerged in hatchery-reared scallop larvae from Chile, threatening scallop aquaculture. In an attempt to mitigate this emerging infectious disease and provide candidates for marker-assisted selective breeding, we tested here the existence of a genetic component of Argopecten purpuratus scallop resistance to the pathogen Vibrio bivalvicida. Through a dual RNA-seq approach we analyzed the basal transcriptome and the transcriptional response to infection in two resistant and two susceptible families as well as the pathogen transcriptomic response to host colonization. The results highlighted a genetic basis in the resistance of scallop larvae to the pathogen. The Vibrio response was characterized by a general metabolic adaptation to the host environment, along with several predicted virulence factors overexpressed in infected scallop larvae with no difference between resistant and susceptible host phenotypes. On the host side, several biological processes were enriched in uninfected resistant larvae. Within these enriched categories, immune-related processes were overexpressed, while morphogenesis, biomineral tissue development, and angiogenesis were under expressed. Particularly, genes involved in immune recognition and antimicrobial response, such as lipopolysaccharide-binding proteins (LBPs), lysozyme, and bactericidal permeability-increasing protein (BPI) were overexpressed in uninfected resistant larvae. As expected, immune-related biological processes were enriched in Vibrio-infected larvae, but they were more numerous in resistant larvae. Overexpressed immune genes in response to infection included several Toll-like receptors, TNF and NF-κB immune signaling genes, and the antimicrobial peptide Big defensin ApBD1. Results strongly suggest that both a front-loading of immune genes and an enhanced antimicrobial response to infection contribute to the resistance, while pathogen infective strategy does not discriminate between host phenotypes. Overall, early expression of host immune genes appears as a strong determinant of the disease outcome that could be used in marker-assisted selective breeding.